2021
DOI: 10.14444/8122
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Anterior Vertebral Body Tethering in Skeletally Mature Children with Adolescent Idiopathic Scoliosis: A Preliminary Report

Abstract: Background: Anterior vertebral body tethering (AVBT) offers a dynamic fusion less correction option for children with adolescent idiopathic scoliosis (AIS). Few existing clinical studies evaluating novel AVBT in skeletally immature children have questioned the midterm efficacy with concerns of overcorrection and curve progression with remaining growth. The current study investigates the effect of this technique in skeletally mature children (Risser ! 4 and Sanders ! 7) with AIS with limited remaining growth po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Yet, in the limited studies inclusive of more skeletally mature patients, overcorrection rates were reduced while maintaining acceptable rates of clinical success in the more mature patient. Hegde et al reported on 10 skeletally mature patients (Sanders ≥7) and found a 71% correction rate of the major Cobb with no incidence of re-operation or conversion to fusion at latest follow-up [ 20 ]. Alanay et al assessed VBT outcomes stratified by Sanders skeletal maturity and found 55% correction of the major Cobb with no incidence of mechanical complications or overcorrection in the Sanders 6–7 cohort as compared to a 60% mechanical complication rate and 80% overcorrection rate in the Sanders 2 cohort in their study [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in the limited studies inclusive of more skeletally mature patients, overcorrection rates were reduced while maintaining acceptable rates of clinical success in the more mature patient. Hegde et al reported on 10 skeletally mature patients (Sanders ≥7) and found a 71% correction rate of the major Cobb with no incidence of re-operation or conversion to fusion at latest follow-up [ 20 ]. Alanay et al assessed VBT outcomes stratified by Sanders skeletal maturity and found 55% correction of the major Cobb with no incidence of mechanical complications or overcorrection in the Sanders 6–7 cohort as compared to a 60% mechanical complication rate and 80% overcorrection rate in the Sanders 2 cohort in their study [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it allows for a good correction on the sagittal plane [3] and it may prevent adjacent segment degeneration [4,5], a common downfall of spine fusion. VBT can be employed both in its growth-modulating form for skeletally immature patients (VBT-growth modulation, VBT-GM) and as a tissue remodelling technique in patients who are approaching or have reached skeletal maturity (VBT-anterior scoliosis correction, VBT-ASC) [6][7][8]. Growth modulation is regulated by the Hueter-Volkmann principle [9,10], while tissue remodelling follows the principles of Wolff's law.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies should be performed on the follow-up results from the time of VBT surgery up to when the patients are skeletally mature, or even longer, and on the poor outcome after VBT that leads to the eventual conversion to PSF. 43…”
Section: Discussionmentioning
confidence: 99%
“…VBT can achieve certain deformity correction during the initial operation, control the patient's spinal growth potential, and make the concave side grow faster than the convex side, thereby realizing continuous correction during subsequent spinal growth while controlling the progression of deformity (Figure 2). Sixteen studies reported the major curve pre-and post-operation and at final follow-up 13,14,22,23,25,[28][29][30][31]34,35,37,38,41,43,45 (Figure 3). Ten studies reported kyphosis angle pre-and post-operation and at final follow-up 13,14,23,28,30,34,37,38,41,45 (Figure 4).…”
Section: Major Curve and Kyphosis Anglementioning
confidence: 99%